A Syntactic Analysis of Sentence Types in a TED-Ed Video Transcript Using Tree Diagrams (Sastra Inggris UNPAM, 2026)
This study analyzed a TED-Ed video transcript to examine the different sentence types used in the video. The study's objectives were to identify the types of sentences and to represent their structures using tree diagrams. The analysis applied Oshima and Hogue's (1998) theory to classify sentence types based on clause structure, and Burton-Roberts' (2016) framework to construct tree diagrams. A qualitative method was employed, as the data were drawn from a text-based transcript. A total of 40 sentences were collected and analyzed. The findings revealed that complex sentences occurred most frequently (23 instances), followed by simple sentences (13 instances), while compound and compound-complex sentences each appeared twice.